THE EMERGENCE AND FORMATION OF THE SUBJECT OF FOLKSTAGE DANCE - A. I. YESHIMBETOVA, (International Journal of Innovations in Engineering Research and Technology, 2021)
This article is a historical excursus into the formation and role of folk-stage dance from its origins to the present. It outlines the contribution of the enthusiastic reformers of character dance - A.F. Bekefi, F.I. Kshesinki, A.V. Shiryaeva, A.I. Bocharova and A.V. Lapukhov. Outstanding dancers, and later teachers, they stood at the origins of the creation of a system for teaching character dance, brought up more than one generation of dancers who continued the formation of folk stage dance as one of the main subjects of a cycle of special disciplines in the vocational training system in ballet schools.